PIERRE TEILHARD DE CHARDIN AND THE PHENOMENON OF MAN (Годишен зборник на Филозофски факултет - Скопје, 2023)
Aware that it is very difficult in one text to review and critically to analyse the entire thought of such a philosopher, Catholic theologian, paleontologist, cultural anthropologist and humanist as Chardin, the author tries to, at least to mention and critically commented on only a few important aspects, parts and dimensions of his polydimensional and transdiscursive thought. Chardin’s discourse is complex and multi-layered. It exceeds the boundaries of special philosophical sciences and disciplines and in its comprehensive holistic systematicity maximally relativizes and makes transparent the border between spiritual/humanistic and natural/biological sciences. At the end of the short review of Chardin, the author presents several critical reviews of his works, which, until today, despite the increased interest in them, unfortunately still remain relatively unknown to the wider philosophical and intellectual public. The text is supported by quoted and referenced philosophical and other professional literature in foreign languages and Macedonian.